Reflexiones del armario - Mora, Tamara De La; Terradillos, Jorge (Cuadernos de Trabajo Social, 2007)
Labeling and categorizing fill the need to repress that which does not fit in with social homogeneity. Stigma acts as an exclusionary factor and acts as an element of group and individual social control An historical overview of the treatment of homosexuality allows us to view its evolution from discrimination to invisibility requiring professional actions which will consequently result in equality and respect for diversity.